Dobór technologii wzmacniania podłoża gruntowego w zależności od warunków geologiczno-inżynierskich. - Chronowski, Jarosław (My University, 2013)
This thesis is dedicated to a accurate specify of the selection of an appropriate method of subsoil strengthening. Various technologies of accomplishing the consolidation from years are used in civil engineering. Increasingly used, modern technologies are used in foundation. Rapid technological development in the last few years improved the performance of different methods of strengthening, which made the ground densification activities are becoming increasingly popular. The need to manage the economic aspects of technology strictly imposed in respect of geologicalengineering conditions and mechanical parameters values in your area. A key element in strengthening the subsoil is correctly diagnosis of ground and adjusted accordingly amplification method, in order to obtain the desired effect. Good solutions is combining techniques of strengthening with each other in simple way, but giving possibility to realistic design investment.

Praca poświęcona jest sprecyzowaniu doboru odpowiedniej metody wzmacniania podłoża gruntowego. Rożne technologie wykonywania wzmocnienia są stosowane w budownictwie wodnym i lądowym. Coraz częściej wykorzystywane są nowoczesne technologie fundamentowania. Szybki rozwój technologiczny w ostatnich kilkunastu lat udoskonalał rożne metody wykonywania wzmocnień, co sprawiło, że czynności dogęszczania podłoża są coraz bardziej popularne. Potrzeba kierowania się aspektami ekonomicznymi narzuca technologie w odniesieniu do warunków geologiczno – inżynierskich i parametrów fizyko – mechanicznych na danym obszarze. Kluczowym elementem wzmacniania podłoża gruntowego jest prawidłowe rozpoznanie gruntu i odpowiednio dopasowana metoda wzmocnienia, celem otrzymania żądanego efektu. Dobrymi rozwiązaniami jest łącznie ze sobą technik wzmacniania w sposób prosty, lecz dający możliwość realistycznego zaprojektowania inwestycji.
Selection of subsoil consolidation technology depending on geological engineering conditions
Keywords: wzmocnienie; technologia; podłoże gruntowe; geologia inżynierska; consolidation; technology; subsoil; geological engineering